Noni Juice Improves Serum Lipid Profiles and Other Risk Markers in Cigarette Smokers. (11th October 2012) - Wang, Mian-Ying; Peng, Lin; Weidenbacher-Hoper, Vicki; Deng, Shixin; Anderson, Gary; West, Brett J.
Abstract : Cigarette smoke-induced oxidative stress leads to dyslipidemia and systemic inflammation. Morinda citrifolia (noni) fruit juice has been found previously to have a significant antioxidant activity. One hundred thirty-two adult heavy smokers completed a randomized, double blind, placebo-controlled clinical trial designed to investigate the effect of noni juice on serum cholesterol, triglyceride, low density lipoprotein cholesterol (LDL), high density lipoprotein cholesterol (HDL), high-sensitivity C-reactive protein (hs-CRP), and homocysteine. Volunteers drank noni juice or a fruit juice placebo daily for one month. Drinking 29.5 mL to 188 mL of noni juice per day significantly reduced cholesterol levels, triglycerides, and hs-CRP. Decreases in LDL and homocysteine, as well increases in HDL, were also observed among noni juice drinkers. The placebo, which was devoid of iridoid glycosides, did not significantly influence blood lipid profiles or hs-CRP. Noni juice was able to mitigate cigarette smoke-induced dyslipidemia, an activity associated with the presence of iridoids.